Neural Processing of Spectral and Durational Changes in Speech and Non-speech Stimuli: An MMN Study With Czech Adults - Nudga, Natalia; Urbanec, Josef; Oceláková, Zuzana; Kremláček, Jan; Chládková, Kateřina (Frontiers in Human Neuroscience, 2021)
Neural discrimination of auditory contrasts is usually studied via the mismatch negativity (MMN) component of the event-related potentials. In the processing of speech contrasts, the magnitude of MMN is determined by both the acoustic as well as the phonological distance between stimuli. Also, the MMN can be modulated by the order in which the stimuli are presented, thus indexing perceptual asymmetries in speech sound processing. Here we assessed the MMN elicited by two types of phonological contrasts, namely vowel quality and vowel length, assuming that both will elicit a comparably strong MMN as both are phonemic in the listeners’ native language (Czech) and perceptually salient. Furthermore, we tested whether any of those phonemic contrasts is processed asymmetrically, and whether the asymmetries are acoustically or linguistically conditioned. The MMN elicited by the spectral change between /a/ and /ɛ/ was comparable to the MMN elicited by the durational change between /ɛ/ and /ɛː/, suggesting that both types of contrasts are equally important for Czech listeners. Furthermore, the spectral change in vowels yielded an asymmetrical pattern manifested by a larger MMN response to the change from /ɛ/ to /a/ than from /a/ to /ɛ/. The lack of such asymmetry in the MMN to the same spectral change in complex tones spoke against an acoustically-based explanation, indicating that it may instead have been the phonological properties of the vowels that triggered the asymmetry. The potential phonological origins of the asymmetry are discussed within an established framework, and conclusions are drawn about the perceptual relevance of the place and height features for the Czech /ɛ/-/a/ contrast.